Implementasi Algortima C4.5 Menentukan Pola Berangkatan Jamaah Haji - Fricles Ariwisanto Sianturi; Mina Kumari; Erlina Laian (CV. Utility Project Solution, 2022)
Determination of the Hajj Pilgrim Departure Pattern is currently very much needed by the Haj organizers, especially at the Office of the Ministry of Religion Lubuk Pakam because the schedule of pilgrims' departure is still not regular, causing accumulation of data on pilgrims who will be departed to the holy land, but with The number of pilgrims who will depart for the pilgrimage is made to determine the pattern of Hajj departure with the C4.5 Algorithm to make it easier for the hajj organizer staff to determine what age should be sent to the holy land.